Global financial stability report : market developments and issues - International Monetary Fund; International Monetary Fund. (Washington, DC : International Monetary Fund, 2006)
This report assesses global financial market developments with a view to identifying potential systemic weaknesses. It seeks to play a role in preventing crises, thereby contributing to global financial stability and to sustained economic growth of the IMF's Department
"September 2006." - Market Developments and Issues
Includes bibliographical references.
nmn 13/05/13; osa 24/09/13; oif 21/05/14, opc11/03/15
Ref/Loans
Keywords: Capital market; International finance; Economic stabilization